2009
DOI: 10.7751/telopea20095826
|View full text |Cite
|
Sign up to set email alerts
|

The genus Cycas (Cycadaceae) in Indonesia

Abstract: The genus Cycas is reviewed for Indonesia. Ten species are enumerated, two of them new (C. sundaica, C. montana). Lectotypes are designated for Cycas Subsection Endemicae, C. glauca, C. circinalis subsp. riuminiana var. curranii forma maritima J.Schust. The species are placed within an infrageneric classification previously outlined. Distribution of all taxa is mapped, and a key to species provided. Extensions into Malaysia (C. edentata) and Papua New Guinea (C. apoa, C. papuana, C. scratchleyana) are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…For the remaining two sections, Wadeae is a relictual section endemic to Philippines (Lindstrom et al, 2008). The full range of the section Cycas is from India and southern Indochina south to Australia and from East Africa east to Tonga (Lindstrom & Hill, 2007;Lindstrom et al, 2009…”
Section: The Distribution Of Cycasmentioning
confidence: 99%
See 1 more Smart Citation
“…For the remaining two sections, Wadeae is a relictual section endemic to Philippines (Lindstrom et al, 2008). The full range of the section Cycas is from India and southern Indochina south to Australia and from East Africa east to Tonga (Lindstrom & Hill, 2007;Lindstrom et al, 2009…”
Section: The Distribution Of Cycasmentioning
confidence: 99%
“…Six classification sections are now recognized in the genus Cycas (Table ): four in Hill (), an additional one in Lindstrom, Hill, and Stanberg () and another one in Lindstrom, Hill, and Stanberg (). According to Hill (), 17 species from section Stangerioides distributed in China and C. multifrondis D. Yue Wang was treated as hybrid swarm of C. dolichophylla K.D.…”
Section: Current Status Of Cycasmentioning
confidence: 99%
“…In addition, multiple extant Asian cycad species, including C. taitungensis , are allopatric and restrictedly distributed with small population sizes [3640] and is considered as relicts from glacial refugia [8]. The small population size and geographic isolation from other populations increase the effect of genetic drift resulting in species divergence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have suggested that Borneo has high biodiversity and endemism because it is a 'cradle' for diversification (Klaus et al 2013, Grismer et al 2016, Williams et al 2017). However, Borneo has only a single Cycas species, the coastally distributed C. edentata (Lindstrom et al 2009). This species arose from dispersal in the last one million years (Fig.…”
Section: The Impact Of Time and Diversification Rates On Richness Patternsmentioning
confidence: 99%